Pemanfaatan Maggot Black Soldier Fly dalam Pengolahan Sampah Organik di Wilayah Kampung Manglayang, Desa Cihanjuang RT001/RW003 - Yuningsih, Rima; Murtafi’ah, Ni’matul; Aeni, Suci Rizki Nurul (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
Waste is still a big problem in various parts of Indonesia, including in the West Java area. According to the West Java Provincial Environment Agency (2024), waste from all districts and cities in the West Java area reaches 25,000 tons per month. Organic waste management in Manglayang Village only relies on cleaners who will transport garbage every week, during a week the garbage is allowed to accumulate in front of the yard so that it causes an unpleasant odor and a lot of flies. The purpose of this study is to reduce organic waste by the bioconversion method which uses larvae to transform organic waste. This research uses the Participaory Action Research technique, namely by approaching socialization and discussion with the community. The results of the study showed the effectiveness of maggot in degrading organic waste for 21 days as much as 18 kilograms with 56 grams of ungranulated waste. The use of BSF maggot in managing organic waste in Manglayang Village 003/001 can be chosen as an alternative to reduce waste which is a problem.